Kontelasi Kelayakan Pembiyaan Kur Di Bank Syariah Indonesia KCP Lumajang Imam Bonjol - Rendy Ilyas Febriansyah; Roni Subhan (Jurnal Ekonomi dan Bisnis Digital, 2023)
This research aims to determine the constellation or description of the wealth of People's Business Credit (KUR) financing at Bank Syariah Indonesia Lumajang Imam Bonjol Sub-Branch Office. The research method used is a qualitative method with descriptive research type. The data collection techniques used were interviews, observation and documentation. This research explains that the feasibility constellation of KUR financing consists of 6 stages, namely: registration, bi-checking, survey, analysis, approval and disbursement. Where the bank analysis stage uses 5 aspects, namely: character, capital, capacity, collateral and economic conditions. From the steps taken it can be concluded that the BSI Lumajang Imam Bonjol sub-branch office prioritizes comfort, speed, prudence, transparency and security.